Notas ficológicas. I. Primer registro de Cutleria cylindrica Okamura (Cutleriaceae, Phaeophyta) para las costas del Pacífico mexicano - Aguilar Rosas, Raul (Instituto de Ecología, A.C., 1994)
Cutleria cylindrica Okamura, a marine brown macroalga formerly known only from Japan and California (U.S.A.), is reported from the northwestern coast of Baja California, México. Both species of the genus known from the North American Pacific coast are thus present in Mexico. Ecological and morphological observations are included.